Peripheral Odontogenic Fibroma- Case Series of a Rare Benign Tumor - Dawadi, Asmita; Lamichhane, Simant; Humagain, Manoj; Poudel, Pratibha; Bhusal, Sita (Journal of Nobel Medical College, 2022)
Peripheral odontogenic fibroma (POdF) is a rare benign odontogenic tumor of ectomesenchymal origin which is composed of fibrous connective tissue containing islands, strands or cords of odontogenic epithelium. The lesion is more common among females, commonly seen between the second to fourth decades of life, mostly affecting the anterior region of mandible. Clinically, it may present similar characteristics with other more common gingival lesions such as pyogenic granuloma, peripheral ossifying fibroma and peripheral giant cell granuloma. So, histopathological examination is required for accurate diagnosis. We present here three rare clinical cases of peripheral odontogenic fibroma and their management by complete excision of the lesion with good postoperative outcomes.